Firm responses to high-speed internet - Henrike Steimer (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2020)
Does access to the broadband internet stimulate firm growth? In this paper, I analyze within-firm growth of established firms caused by the access to faster internet using geocoded social-security data. I identify firm responses to the access to the first generation of broadband internet and later speed upgrades by exploiting technological peculiarities of the broadband internet network. I find that firms with access to the first generation of broadband internet grow more slowly in employment while keeping their output growth constant. They reduce the share of low-skilled employment in their workforce. Further, I find that firms that receive access to later speed upgrades grow more in revenues and employment than firms that got access to the first generation of broadband internet but not to the upgrades. When getting access to higher internet speed, firms over-proportionally increase medium-skilled employment.
Keywords: D22; J23; O33; 330; ICT; internet; firm growth; skill-bias; technology